Analysis of heat transfer mechanism in supercritical fluids from the aspect of pool heating - Liu, Minyun; Liu, Shenghui; Xi, Dapeng; Huang, Shanfang; Huang, Yanping (Frontiers in Energy Research, 2023)
For the special phenomena of heat transfer deterioration or enhancement in supercritical fluid heat transfer, existing research still presents inconsistent opinions. In this study, we perform an analysis of the property changes, and present new understandings for pseudo-boiling theory. More importantly, essential differences between subcritical boiling and supercritical pseudo-boiling are highlighted; the critical factors being thermodynamic instability and stability. For isothermal heating cases, pseudo film boiling can be regarded as an extension of near-critical boiling. Moreover, pseudo nucleate boiling only appears in non-isothermal heating cases and is strongly dependent on the heater geometry, materials, etc. A coupled level-set and volume-of-fluid method is used to simulate the near-critical film boiling of carbon dioxide at pressures of 7.0 and 7.37 MPa. In comparison, supercritical cases at a pressure of 7.5 MPa are the natural convections of single-phase fluid with variable physical properties. The numerical results indicate the similar motions of low-density fluids in subcritical and supercritical cases. All results are consistent with prior experiments, providing a better understanding of the special features of supercritical fluid heat transfer.